Adaptation of the Psychological Capital Questionnaire (PCQ-12S) - Olefir , Valerii Oleksandrovych; Bosniuk , Valerii Fedorovych (Insight: the psychological dimensions of society, 2023)
The purpose of the article is to develop a short Ukrainian-language version of the psychological capital questionnaire based on a 24-pointoriginal test for use in higher education. Despite the construct’s absolute practical value in the context of various life spheres, including academic one, there is currently no instrument for its measurement, which is of concern and requires domestic scientists to fill a gap. Methods. Two bilingual psychologists conveyed PCQ-24 from English into Ukrainian via reverse translation. Based on a preliminary analysis,24 questions were reduced to 12, which had the highest factor loadings, increased scale internal reliability, rendered crucial aspects of the construct, and kept an optimal balance of the number of items for each questionnaire component. 500 students participated in the study via the online service Google Forms. Data analysis was conducted using the statistical software environment R and Rstudio. Results. Confirmatory factor analysis (CFA) made it possible to establish that of the three alternative models of the PCQ-12S structure, a hierarchic alone best corresponds to empirical data as it conceptualizes psychological capital as a latent factor of the highest level with four first-order factors: self-efficacy, hope, resilience, and optimism. It allows calculating points for individual factors and an integral indicator – psychological capital. The model was also analyzed for compliance with psychometric characteristics. As a result, various statistical methods proved that the diagnostic scale of psychological capital has high reliability in the academic context, confirmed convergent and discriminant validity, as well as measurement invariance by gender. Conclusions. PCQ-12S is an economical means of measuring psychological capital and its components in university students. The relevant scale has acceptable and well-recognized psychometric characteristics and is recommended for use in higher education to solve both theoretical and practical problems.
Keywords: self-efficacy, hope, resilience, optimism, psychometric characteristics